2020
DOI: 10.3892/mmr.2020.11113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SIRT1 activators and inhibitors on CD44+/CD133+‑enriched non‑small cell lung cancer cells

Abstract: lung cancer is one of the most commonly diagnosed cancers and it is associated with high rates of morbidity and mortality. Metastasis and relapse of the tumor depend on the survival and proliferation of lung cancer stem cells (lcScs). The ability to identify cScs may prevent recurrence and lead to more effective treatments. Sirtuins are a group of deacetylases that include seven variants (SirT1-7), with sirtuin 1 (SirT1) being the most intensively investigated. evidence suggests that SIRT1 is both a tumor-supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…SIRT1 has been reported to regulate neovascularization by reducing the transcriptional activity of P53 by deacetylation of its lysine residues ( 85 , 86 ). A study investigating the effects of SIRT1 activators and inhibitors on CD44+/CD133+-enriched NSCLC cells reported that SIRT1 can deacetylate the tumor suppressor protein P53, thereby decreasing its activity ( 87 ). Meanwhile, the modulation of SIRT1 expression by resveratrol promoted the collateral sensitivity of drug-resistant ABCB5- and mutation-activated EGFR overexpressing cells ( 88 ).…”
Section: Sirtuin 1 (Sirt1) Correlates With the Occurrence And Development Of Nsclcmentioning
confidence: 99%
“…SIRT1 has been reported to regulate neovascularization by reducing the transcriptional activity of P53 by deacetylation of its lysine residues ( 85 , 86 ). A study investigating the effects of SIRT1 activators and inhibitors on CD44+/CD133+-enriched NSCLC cells reported that SIRT1 can deacetylate the tumor suppressor protein P53, thereby decreasing its activity ( 87 ). Meanwhile, the modulation of SIRT1 expression by resveratrol promoted the collateral sensitivity of drug-resistant ABCB5- and mutation-activated EGFR overexpressing cells ( 88 ).…”
Section: Sirtuin 1 (Sirt1) Correlates With the Occurrence And Development Of Nsclcmentioning
confidence: 99%
“…Thus, targeting at SIRT1 may be a good way for regulating the occurrence and development of LC. 38 VHL expression may be an important biological indicator of the occurrence, development, clinical biological behavior, and prognosis of LC. 39 Studies have found that LEF1 overexpression leads to enhanced LC cell proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%